Efeitos do disseleneto de difenila na atividade da enzima δ-aminolevulinato desidratase e em parâmetros bioquímicos de ratos com diabetes mellitus tipo 1 - Oliveira, Carolina Quatrin (2004)
The hyperglycemia and oxidative stress are factors strongly involved on development of many disorders that characterize the Diabetes Mellitus. It is known that some organic and inorganic selenium compounds are potent antioxidant agents and present similar activity to the insulin in the control of hyperglycemia. Base on these data, the present study evaluated the effect of the organoselenium compound, diphenyl diselenide, on the δ-ALA-D activity and biochemical parameters of diabetic type 1 rats, induced by alloxan. The animals were treated with 6 consecutives doses of diphenyl diselenide (10 mg/kg, s.c) administrated before (pretreatment) or after (post-treatment) diabetes induction. Diphenyl diselenide presented inhibitory effect per se on hepatic and renal δ-ALA-D activity. However, this effect was not verified on other tissues. Regarding aminotransaminases, there was no difference on aminotransaminases for both diphenyl diselenide pre and post treated rats at the first week of the induction. Besides, the results suggest that diphenyl diselenide seem to possess ability to regulate the levels of plasma glucose and serum fructosamine altered in diabetic animals. Thus, diphenyl diselenide was not effective in protecting δ-ALA-D inhibition verified in this dose and protocol. However, this compound seems to possess hepatic protector effect and property of reducing the hyperglycemia. Considering that diphenyl diselenide has a simple chemistry structure and it is easily prepared, new studies could be carried out to investigate other pharmacological properties as well the mechanisms involved in diphenyl diselenide effects.